Self Efficacy Among Patients with Diabetes Mellitus Type 2 in Community Health Center - Widiastuti, Linda; Wati, Liza; Sari, Komala; Atrie, Utari Yunie (Indonesian Journal of Global Health Research, 2024)
Type 2 diabetes mellitus (T2DM) is a growing global health problem, especially in Indonesia. Self-efficacy or an individual's belief in their ability to manage their health, plays an important role in diabetes management. This study aims to describe the level of self-efficacy in T2DM patients at Toapaya Health Center and identify factors that influence this self-efficacy. This study used a descriptive design with purposive sampling, involving 51 respondents who met the inclusion criteria. Data were collected through the Diabetes Management Self-Efficacy (DMSE) questionnaire and analyzed using frequency distribution. The results showed that 27 respondents (52.94%) had low self-efficacy, while 24 respondents (47.06%) had high self-efficacy. Internal and external factors that contribute to the level of patient self-efficacy, such as knowledge, personal experience, social support, and interaction with health workers, were identified. This study emphasizes the importance of improving the self-efficacy of T2DM patients through education and social support programs.